REMARKS FROM TOURISM PLANNING AND SUSTAINABLE TOURISM - A BIBLIOMETRIC STUDY - Luis Mota; Sérgio Teixeira; Frederica Gonçalves (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2018)
Tourism is emphasized as one of the sectors with the greatest potential for expansion on a global scale; therefore, it is important to understand related factors regarding tourism planning and sustainability. The main contribution of this study is to identify research trends linked to the keywords, respective gaps and specific needs for future scientific research within the research field of tourism planning and sustainable development. Using VOSviewer Software and applying bibliometric techniques, visualization maps of the intellectual structure were created for a systematic review of the literature. The number of articles published and the number of annual citations for the period 1997 to 2017 of the Web of Science database were used for this purpose. The results draw attention to multiple research clusters focused on the intelectual structure of tourism planning and sustainable development.